Comparison of twelve human milk oligosaccharides in mature milk from different areas in China in the Chinese Human Milk Project (CHMP) study. (30th November 2022) - Zhang, Wenyuan; Vervoort, Jacques; Pan, Jiancun; Gao, Peng; Zhu, Huiquan; Wang, Xiaodan; Zhang, Yumeng; Chen, Baorong; Liu, Ying; Li, Yuanyuan; Pang, Xiaoyang; Zhang, Shuwen; et al.
Highlights: The concentration of twelve human milk oligosaccharides varied depending on geographical location. Environmental factors result in the differences in HMOs concentrations. Maternal anthropometric indexes and diet correlated with HMOs compositions. Abstract: Human milk oligosaccharides (HMOs) act as a vital role in the development of infant's gut microbiome and immune function. This study aimed to measure 12 oligosaccharides in milk from Chinese donors (n = 203), and evaluated the influences of multiple factors on the HMOs profiles. The results indicated that concentrations of 6′-sialyllactose were the highest among 12 oligosaccharides (2.31 ± 0.81 g/L). HMOs concentrations varied depending on geographical location. Latitude was observed to be related to concentrations of Lacto- N -neohexaose, lacto- N -fucopentaose III, 3′-sialyllactose (r = -0.67, r = +0.63 and r = +0.50, respectively). Environmental factors like seasons correlated with lacto- N -difucohexaose Ⅱ, Lacto- N -neohexaose and 2′-fucosyllactose (r = -0.47, r = -0.4, r = -0.35, respectively). Several HMOs concentrations were correlated with maternal diet. As a consequence, the HMOs profiles measured were influenced by geographical, environmental, maternal anthropometric as well as dietary factors.